African language-speaking plurilingual students’ writing in English: Shifting the focus from ‘error’ to ‘variation’ - Mona, Msakha; Hurst Harosh, Ellen (Critical Studies in Teaching and Learning, 2024)
The study aims to address epistemological erasure by challenging the way students’ knowledge is assessed in written assessments. The problem lies in assessment practices that do not consider the social and linguistic context of students’ writing, particularly for plurilingual speakers of English. The study analysed a set of essays by plurilingual students to make sense of ways in which the students’ backgrounds found expression in their English writing. Using the decolonial concept of locus of enunciation, the study found that features considered "errors" in English essays are often influenced by students’ plurilingual backgrounds. Thus, the study argues for a shift from framing plurilingual students’ writing as “error”, to “variation” which would be accommodated by a true translanguaging approach.